Genetically encoded mediators for sonogenetics and their applications in neuromodulation - Wang, Hsien-Chu; Phan, Thi-Nhan; Kao, Chi-Ling; Yeh, Chih-Kuang; Lin, Yu-Chun (Frontiers in Cellular Neuroscience, 2023)
Sonogenetics is an emerging approach that harnesses ultrasound for the manipulation of genetically modified cells. The great penetrability of ultrasound waves enables the non-invasive application of external stimuli to deep tissues, particularly advantageous for brain stimulation. Genetically encoded ultrasound mediators, a set of proteins that respond to ultrasound-induced bio-effects, play a critical role in determining the effectiveness and applications of sonogenetics. In this context, we will provide an overview of these ultrasound-responsive mediators, delve into the molecular mechanisms governing their response to ultrasound stimulation, and summarize their applications in neuromodulation.